PENERAPAN TEKNIK KOLASE UNTUK MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI TK AL-HIDAYAH BINAMANG KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Dahnia Afrida; Isjoni Isjoni; Yeni Solfiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the increase fine motor skill in children aged 5-6 years through techniques collage kindergarten Al-Hidayah Binamang XII Koto Kampar District. This study is kind studies using action research or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. Subject empirically n are children aged 5-6 years who are 16 children in Kindergarten Al-Hidayah. The research data obtained through observation and data analysis was done by using quantitative descriptive analysis. The research shows that techniques a collage can boost fine motor skill in children aged 5-6 years. It can be seen from the increase in the average percentage of the fine motor skill of children in the first cycle by 52,8% which is the criteria began to develop (MB) and an increase of 60% in the second cycle to 83,4% which is very good at developing criteria (BSB). So, techniques a collage can improve fine motor skill of children aged 5-6 years in -Hidayah Binamang XII Koto Kampar DistrictKeywords : Fine Motor Skill, Techniques a collage